Cities and the Anthropocene: Urban governance for the new era of regenerative cities - Thomson, Giles; Newman, Peter (SAGE PUBLICATIONS LTD, 2020)
The emerging ‘grand challenges’ of climate change, resource scarcity and population growth present a risk nexus to cities in the Anthropocene. This article discusses the potential that rapid urbanisation presents to help mitigate these risks through large-scale transitions if future urban development is delivered using evidence-based policies that promote regenerative urban outcomes (e.g. decarbonising energy, recycling water and waste, generating local food, integrating biodiversity). Observations from an Australian case study are used to describe urban governance approaches capable of supporting regenerative urbanism. The regenerative urbanism concept is associated with macro-scale urban and transport planning that shapes different urban fabrics (walking, transit, automobile), as the underlying infrastructure of each fabric exhibits a different performance, with automobile fabric being the least regenerative. Supporting urban systems based upon regenerative design principles at different scales (macro, meso and micro) can deliver deep and dramatic outcomes for not just reducing the impact of the grand challenges but turning them into regenerative change. In combination, these approaches form the cornerstone of regenerative cities that can address the grand challenges of the Anthropocene, while simultaneously improving livability and urban productivity to foster human flourishing.